Mining and natural hazard vulnerability in the Philippines digging to development or digging to disaster? - Holden, William N. (William Norman) 1962-; Jacobson, R. Daniel (Anthem Press, 2012)
"This book explores how natural hazards in the Philippines can amplify the environmental harm prevalent in mining and pose a substantial threat to the livelihoods of archipelago's poor, who depend upon subsistence agriculture and subsistence aquaculture."--Publisher's description.